2015
DOI: 10.1186/s12955-015-0281-x
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life in Parkinson’s disease: a cross-sectional study focusing on non-motor symptoms

Abstract: BackgroundThe objective of this study was to investigate factors affecting health-related quality of life (HRQoL) among Estonian persons with Parkinson’s disease (PD).Methods268 persons with PD were evaluated using: the Movement Disorder Society Unified Parkinson’s Disease Rating Scale (MDS-UPDRS); the Hoehn and Yahr scale (HY); the Schwab and England Activities of Daily Living scale (SE-ADL); the Beck Depression Inventory (BDI); the Mini Mental State Examination (MMSE); the Parkinson’s Disease Questionnaire (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
70
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(90 citation statements)
references
References 42 publications
(48 reference statements)
10
70
1
3
Order By: Relevance
“…Also, they reported feeling loss of control over the specific activities in which they engaged. This might suggest a negative impact of hobbyism and punding in PD on subjective wellbeing, and recently, Kadastik-Eerme et al [31] showed that non-motor symptoms in PD including impulse control disorders are associated with decreased health-related quality of life. Future studies are needed to assess the extent to which time consumption on and pre-occupation with ICB's affects quality of life and overall everyday functioning.…”
Section: Discussionmentioning
confidence: 99%
“…Also, they reported feeling loss of control over the specific activities in which they engaged. This might suggest a negative impact of hobbyism and punding in PD on subjective wellbeing, and recently, Kadastik-Eerme et al [31] showed that non-motor symptoms in PD including impulse control disorders are associated with decreased health-related quality of life. Future studies are needed to assess the extent to which time consumption on and pre-occupation with ICB's affects quality of life and overall everyday functioning.…”
Section: Discussionmentioning
confidence: 99%
“…1 We read with great interest the papers cited in this letter that investigate the comorbidity and mortality of PD, paying a special attention to the cardiac abnormalities, in particular, the sudden unexpected death in PD (SUDPAR). 5 Although the causes of morbidity and mortality are shown to be similar in the general population and in the PD population, it has been shown that the survival is shorter among PD patients. Older age is associated not only with the higher prevalence of PD, but also with other diseases including cardiovascular, gastrointestinal and oncological disorders.…”
Section: Response To the Letter By Scorza Et Almentioning
confidence: 99%
“…3,4 Our earlier cross-sectional study on the healthrelated quality of life of patients with PD showed that women have statistically higher load of comorbidities compared to men, including a significantly higher rate of cardiovascular diseases. 5 Although the causes of morbidity and mortality are shown to be similar in the general population and in the PD population, it has been shown that the survival is shorter among PD patients. 6 Higher burden of comorbidities has shown to be a predictor of death in PD patients.…”
Section: Response To the Letter By Scorza Et Almentioning
confidence: 99%
“…Depression is the most common determinant of reduced quality of life [37]. It has a substantial impact on quality of life of both the patients and their families.…”
Section: Depressionmentioning
confidence: 99%